Study of heavy metal contamination in soils due to human activities - Saffaatul Husna Ismail (School of Environmental Engineering, University Malaysia Perlis, 2012)
An assessment was made on six (6) different site soils based on human activities in the selected sites in Kangar. The concentrations of five (5) heavy metals (Cu, Cd, Ni, Pb and Zn) in these soils were investigated. Soil samples were collected start from November 2011 until January 2012 by considering dry and wet seasons. The first three soil sampling was conducted in dry season, while the next three soil sampling was carried out in wet season. The samples were digested using standard wet digestion method and heavy metal concentrations were determined with atomic absorption spectrophotometer (AAS). The study reveals that the concentrations of heavy metals studied in soils of wet market (WM), mechanic workshop (MW), dumping site (DS), paddy field (PF), car wash (CW) and control site (CS) in dry season were higher than those in wet season. The amount of Cu, Ni and Zn was highest in the top soil of MW during dry (623.7 mg/kg, 30.3 and 491.5 mg/kg respectively) and wet seasons (325.9 mg/kg, 17.2 mg/kg and 356.3 mg/kg respectively). The Pb content was highest in the top soil of CW during dry (833.3 mg/kg) and wet season (544.8 mg/kg). Slightly different with the concentration of Cd in soil of all sites due to the undetectable concentration of this heavy metal in dry season but traceable in wet season.